Caries Experience In Children With Severe Early Childhood Caries - Aneta Munteanu; Rodica Luca; Catalina Farcasiu; Ioana Stanciu (Romanian Society of Oral Rehabilitation, 2012)
ntroduction Caries experience indexes in children with severe early childhood caries (S-ECC) reported in literature are lower in the general population than in children referred to paediatric dental clinics. The aim of the study was to compare different samples of children (two samples from dental clinics and one from general population) from this point of view. Methods Retrospective analysis upon 3 samples of children 5 years old or under: sample A - 685 children (392 boys, 293 girls) referred to Pedodontics Department, Faculty of Dentistry, Carol Davila University, Bucharest, sample B - 233 children (124 boys, 109 girls) examined in a private dental clinic and sample C - 552 children (284 boys, 268 girls) from 12 kindergartens from Bucharest. Prevalence index (IpS-ECC) and caries experience indexes (dmft, dmfs and SiC) from S-ECC children were evaluated. Caries topography was also noted. Data were analyzed using a chi-square test